Dorsal Approach in the Surgical Treatment of Complex Dorsal Dislocation of Index Metacarpophalangeal Joint; a Case Report : Complex Dorsal Dislocation of Index Metacarpophalangeal Joint - Sattari, Shahab Aldin; Sattari, Ali Reza; Heydari, Kamran; Sadat Kiaei, Seyed Matin; Zandrahimi, Farshad; Mohammadpour, Mehdi (Archives of Academic Emergency Medicine, 2022)
Complex metacarpophalangeal (MCP) joint dislocation is an uncommon entity, which occurs following a hyperextension injury. Closed reduction is not feasible due to entrapped volar plate and/or coexisting fractures. Various approaches and techniques have been proposed for treatment of complex MCP dislocation; however, controversies exist over which one is superior. This study describes a right-handed 14-year-old boy who fell on the outstretched hand and sustained a dorsal dislocation of the left index MCP joint. The dislocation was complicated by an epiphyseal metacarpal head fracture with dorsal-ulnar displacement of the osteochondral fragment. The patient underwent open reduction through the dorsal approach, and the metacarpal head was fixed via the two-screw technique. The patient resumed left-hand function after six weeks. At the two-year follow-up, the range of motion and grip strength were normal, the patient was pain-free, and no sign of growth disturbance or joint stiffness was detected. Dorsal surgical approach with screw fixation is a feasible technique for the treatment of complex MCP dislocation, especially when it is complicated by a large epiphyseal head fracture.